2023
DOI: 10.3389/fendo.2023.1117259
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the microbiota-gut-brain axis in response to sleep deprivation and diet-induced obesity

Abstract: IntroductionSleep deprivation (SD) and obesity are common in modern societies. SD and obesity frequently coexist, but research on the combined consequences of SD and obesity has been limited. In this study, we investigated the gut microbiota and host responses to SD and high-fat diet (HFD)-induced obesity. In addition, we attempted to identify key mediators of the microbiota-gut-brain axis.MethodsC57BL/6J mice were divided into four groups based on whether they were sleep deprived and whether they were fed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…SD has been proved to increase Aβ-in the hippocampus, precuneus, thalamus, and cortex, along with neuroinflammation and oxidative stress, and inhibit cholinergic neurons, indicating a direct connection between SD and neuropathological events associated with AD [113]. (3) Stroke: a study showed that SD exacerbates stroke by raising the expression of growth-inhibiting genes, neuroinflammation, and oxidative stress [28,113].…”
Section: Gut-brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…SD has been proved to increase Aβ-in the hippocampus, precuneus, thalamus, and cortex, along with neuroinflammation and oxidative stress, and inhibit cholinergic neurons, indicating a direct connection between SD and neuropathological events associated with AD [113]. (3) Stroke: a study showed that SD exacerbates stroke by raising the expression of growth-inhibiting genes, neuroinflammation, and oxidative stress [28,113].…”
Section: Gut-brain Axismentioning
confidence: 99%
“…Previous research has found that 20% to one-quarter of the population of the United States is forced to face it [16][17][18] because of improper diet [19], pressure [20,21], and increasing brain stimulation by smartphones [1]. Possible adverse outcomes elicited by SD include depression (in a bidirectional relationship with SD) [22][23][24][25][26], obesity [27,28], diabetes [14,29], cardiovascular disease [30,31], cancer [32,33], neurological dysfunction [31,34], and even death [34]. Therefore, a better understanding of the association between SD and human diseases, as well as the underlying mechanisms of action, is of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…According to the consensus of the American Academy of Sleep Medicine and Sleep Research Society, adults should strive for 7 h of nightly sleep while young adults require 9 h. Insufficient sleep due to occupational or recreational activities is classified as sleep deprivation 101 . One study has demonstrated a correlation between sleep deprivation and the gut dysbiosis 102 . In this study, increased sleep deprivation decreased the alpha diversity of the gut microbiome (Supplementary Table 13 )although the differences were not significant, and the gut microbiota structures among the normal sleep (n = 145), more sleep deprivation (n = 131) and less sleep deprivation (n = 207) groups showed a significant difference (Binary-jaccard distance, Adonis, Pr (> F) = 0.029, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothalamic syndrome is also characterized by abnormal eating behavior such as hyperphagia 5 . Patients with hypothalamic lesions often present with higher food inattention, lower statiety and higher restrained eating behavior 7 . However, hyperphagia is not always present in patients with CP, reflecting that in some patients specific hypothalamic nuclei are still intact after treatment 2 .…”
Section: Introductionmentioning
confidence: 99%